Retrospective Analysis of accurate position of Different Implant Systems Using Mucosa-Supported Surgical Templates - Vijapure, Shashank; Nazir, Aaquib; Aghera, Angel; Sahani, Jewel Ipsita; Shah, Harsh; Senta, Nidhi (Journal of Neonatal Surgery, 2025)
Background: Accurate implant positioning is critical for long-term success in implant dentistry. Mucosa-supported surgical templates have gained popularity in edentulous cases due to their non-invasive nature and improved patient comfort. However, limited comparative data exist regarding their accuracy across different implant systems. This study retrospectively evaluates the positional accuracy of three commonly used implant systems when placed using mucosa-supported templates. Materials and Methods: This retrospective study included 45 edentulous patients (mean age: 61.3 ± 8.5 years) who underwent guided implant placement using mucosa-supported stereolithographic templates between 2020 and 2023. Three implant systems were analyzed: System A (n=15), System B (n=15), and System C (n=15). Pre- and postoperative CBCT scans were superimposed using digital planning software to measure deviations at the implant platform, apex, and angular discrepancies. Mean deviations were calculated and statistically analyzed using ANOVA and post hoc Tukey tests (significance set at p<0.05). Results: System A showed a mean coronal deviation of 1.45 ± 0.38 mm, apical deviation of 1.78 ± 0.52 mm, and angular deviation of 4.2° ± 1.1°.System B recorded a mean coronal deviation of 1.21 ± 0.33 mm, apical deviation of 1.55 ± 0.41 mm, and angular deviation of 3.5° ± 0.9°.System C had the lowest deviations, with coronal deviation at 1.02 ± 0.27 mm, apical deviation at 1.29 ± 0.36 mm, and angular deviation of 2.8° ± 0.7°.Statistical analysis showed significant differences between the systems (p<0.05), with System C demonstrating superior positional accuracy. Conclusion: Within the limitations of this retrospective study, System C exhibited significantly higher positioning accuracy when used with mucosa-supported surgical templates compared to Systems A and B. These findings underscore the importance of system-specific template compatibility and suggest that clinicians may achieve enhanced outcomes by selecting implant systems optimized for mucosa-supported guidance.